"Evening chronotype associates with increased triglyceride levels in young adults in two independent populations". Issue 4 (April 2021) - Aguilar-Galarza, Adriana; García-Gasca, Teresa; Mejía, C.; Díaz-Muñoz, Mauricio; Pérez-Mendoza, Moisés; Anaya-Loyola, Miriam Aracely; Garaulet, Marta
Summary: Background & aims: Evening chronotype has been linked with obesity, diabetes and metabolic syndrome (MetS) in middle-aged and older adults. However, few studies have analyzed this association in young adults. The aim of this study was to assess potential associations between individual chronotype and cardiometabolic outcomes in young adults of two independent populations from Europe and America. Methods: Total population comprised 2 223 young adults (18–29 years old), 525 from Spain (Europe) and 1 698 from Mexico (America). Anthropometric, body composition and biochemical analyses were performed. Circadian preference was determined using the Morningness-Eveningness Questionnaire (MEQ). Results: In these two young adult populations, a higher metabolic risk was found in those individuals with evening chronotypes, whereas those with neither or morning chronotypes showed lower cardiometabolic risk. Evening chronotypes showed lipid alterations with increased levels of triglycerides in both populations, VLDL-c in Spaniards and total cholesterol and LDL-c in Mexicans. Among the Mexican population, evening chronotypes showed higher MetS risk and more obesity traits than the other two chronotypes; no significant differences for the same comparison were found among the equivalent Spanish chronotypes. Evening chronotypes showed lower carbohydrates and higher fat intake in Spaniards, while they had lower fiber intake in Mexicans. The associations between MEQ score and cardiometabolic risk were independent of the dietary characteristics. Lifestyle factors differed among chronotypes with more smokers and habitual drinkers among evening chronotypes than in neither or morning chronotypes ( P < 0.05). Conclusions: This study performed in two American and European independent populations shows that even in apparently healthy young adults, evening chronotypes have increased cardiometabolic risk and lipid alterations as compared to neither or morning chronotypes.